The effects of EMU on structural reforms in labour and product markets - Romain Duval; Jørgen Elmeskov (European Central Bank (ECB), 2006)
Will EMU accelerate or retard structural reform in labour and product markets? The theoretical literature is ambiguous. New descriptive evidence provided in this paper suggests that euro-area countries have made relatively good progress in structural reform. However, it is much less clear whether progress can be ascribed to EMU membership. To explore further the influence of monetary regime, the paper undertakes an econometric examination of the likelihood that countries undertake reform in five specific areas of labour and product market policies. Based on pooled cross-country/time series Probit regressions covering 21 countries and the period 1985-2003, it is found that structural reform is strengthened by high unemployment, crisis, healthy public finances, reforms in other policy fields and small country size. Further, countries that pursue fixed exchange-rate regimes or participate in monetary union, and therefore have little or no monetary autonomy, appear to undertake less reform – with the effect possibly being concentrated on large countries.
Keywords: D7; O52; 330; EMU; euro; labour market; political economy; product market; reforms; Wirtschaftsreform; Arbeitsmarktflexibilität; Eurozone; Schätzung; EU-Staaten